PEMATANGAN GONAD CALON INDUK IKAN SEPAT MUTIARA (Trichogaster leeri Blkr) DALAM KERAMBA DENGAN PADAT TEBAR BERBEDA - Sukendi, Sukendi; Putra, Ridwan Manda; Asiah, Nur (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
This study aims to determine the best stocking solid in the gonad maturation of Tricho-gaster leeri Blkr in cages placed in ponds. Cage size used is 1 x 1 x 1 m were placed in thepond Fisheries and Marine Science Faculty, Riau University with a solid stocking respectivelyP1 = 30 fishes/cage, P2 = 40 fishes/cage and P3 = 50 fishes /cage. The fish were reared for 6(six) weeks, during maturation of fish feed shrimp pellets + vitamin E. Maturation observa-tions conducted each week by taking 20% of the samples. Parameters measured were maturitylevel, gonado somatic index (GSI), fecundity, egg diameter, semen volume, and mortality.The results showed that the best treatment was P1 = 30 fishes/cage produce attainment gonadmaturation (TKG IV) was 2 fishes, gonado somatic index (GSI) was 8.36 %, fecundity was1004 eggs, egg diameters was 0.66 mm, semen volume was 0.0173 ml and mortality was 2fishes.]